Modeling the Yogyakarta International Airport (YIA) Area Flood Control System Using EPA SWMM 5.1 - Ulumuddin, Muhammad Ihya; Istiarto, Istiarto; Wignyosukarto, Budi Santoso (Universitas Negeri Yogyakarta, 2023)
Yogyakarta International Airport (YIA) is a new airport that operates in the Special Region of Yogyakarta, located in Temon District, Kulon Progo Regency. The presence of the airport will undoubtedly bring various benefits, such as increasing economic activities in the area around the airport. However, the location has a problem, namely the risk of flooding. Flooding can affect activities around the airport, such as freight forwarding activities and access to or from the airport. Based on this problem, efforts are needed to prevent the flood that occurs does not have an impact on the activities of YIA airport and the surrounding area. In this case, the researcher used the EPA SWMM program in modeling the drainage system at the site under study. Modeling the point of occurrence of flooding will make it easier to normalize and add embankments to the channel. Modeling with EPA SWMM 5.1 requires input data such as rain distribution data, watershed characteristics, and the transverse appearance of the drainage channel. The results showed an overflow in the 15 drainage channels studied. The causes of overflow are high surface runoff and sedimentation based on channels and backwaters. Efforts to overcome by normalizing and adding embankments are sufficient to overcome flooding in several channels. Meanwhile, for channels that are still experiencing flooding, other countermeasures, such as retention ponds, are needed.